Synthesis, Anticancer Activity, Docking Calculations and Hydrolytic Stability Studies of Bioconjugates of Monofluorenated Analogue of BIM- 23052 - Danalev, Dancho; Iliev, Ivan; Borisova, Dessislava; Dzimbova, Tatyana; Pajpanova, Tamara; Zaharieva, Zdravka; Karadjova, Veronika; Foteva, Tsvetelina; Naydenova, Emilia (Protein and Peptide Letters, 2022)
Background: The fight against cancer has started since its discovery and has not subsided to nowadays. Currently, the hybrid molecules have become a promising alternative to the standard chemotherapeutics for the treatment of multi-causal diseases, including cancers. Objective: Herein, we report the synthesis, biological evaluation, mathematical docking calculations and hydrolytic stability of the new bioconjugates of monofluorinated analogues of BIM-23052, containing second pharmacophore naphthalimide, caffeic acid or the tripeptide Arg-Gly-Asp. Methods: All new molecules are obtained using standard peptide synthesis on solid support. Anticancer potential is studied against a panel of tumor cell lines included human mammary carcinoma cell lines MCF-7 (ER+, PR+ and Her-2-); MDA-MB-231 (ER-, PR- and Her-2-), as well as cell lines BALB 3T3 (mouse embryonic fibroblasts) and MCF-10A (human breast epithelial cell line). Results: The IC50 values found in the MCF-10A cell line assay were used to calculate the selective index (SI). The highest SI relative to MCF-7, with a value of 2.62 is shown by the compound Npht- Gly-D-Phe-Phe(4-F)-Phe-D-Trp-Lys-Thr-Phe-Thr-NH2. In MCF-10 cells, the weakest antiproliferative effect was caused by the same compound (IC50 = 622.9 ± 23.91 μM), which makes this analogue a good candidate for the new anticancer medical drug. Unfortunately, the hydrolytic stability studies reveal that this bioconjugate is the most unstable of hydrolysis under physiological conditions in the body. Conclusion: Even with lower anticancer activity and selectivity in comparison with Npht-Gly-DPhe- Phe(4-F)-Phe-D-Trp-Lys-Thr-Phe-Thr-NH2, the compound Arg-Gly-Asp-D-Phe-Phe(4-F)-Phe- D-Trp-Lys-Thr-Phe-Thr-NH2 is the best candidate between three investigated bioconjugates for practical application due to combination of activity and stability profiles. Mathematical docking calculation also reveals that synthesized bioconjugates show selectivity according to different somatostatin receptors on the surface of different cell lines.
Keywords: hydrolytic stability